The epidemiology of alimentary diseases - Duggan, John M. (Springer, 2006)
In offering this book to what we hope will be interested readers, we have several aspirations. We have aspired to present to students and clinicians a rather narrow view of epidemiology concentrating on the causal factors and setting of the more usual gastroenterological problems and giving greater space to conditions of importance for which major knowledge of causation andcourse is available. Part of the rationale is thebelief that modern medicine lays excessive emphasis on therapy with increasingly expensive, and in many cases, dangerous drugs and too little emphasis on the causes and avoidance of disease. We are of the view that traditional views handed st down through generations of clinicians need scrutiny worthy of 21 century medicine whose currency includes topics like nanomoles, megabytes and logistic regression. We hope that clinicians will see that there is often a practical application to the findings of epidemiological exploration and that what passes for canonical knowledge is so often unsubstantiated myth and are fully aware of the reluctance of organized medicine to reject old paradigms in favor of the new, matched by an often uncritical enthusiasm for new therapies. Our researches have increased our belief in the major role of social factors especially diet, both in quantity and quality in many disorders and that clinicians have a responsibility to provide appropriate advice to policy makers as well as patients. Epidemiology and clinical practice - Some spidemiological concepts - Genetics and the gut - Reflux oesophagitis - Carcinoma of the oesophagus - Peptic ulcer - Chronic gastritis/gastric erosions - Functional dyspepsia - Carcinoma of the stomach - Coeliac disease/celiac sprue - Lactase deficiency - Irritable bowel syndrome - Traveller’s diarrhoea - Food poisoning/bacterial infections of the gut - Parasitic diseases of the gut - Acute appendicitis - Rare and unusual syndromes, Polyposis syndromes and polyps - Benign colorectal neoplasms - Adenoma - Malignant colorectal Neoplasm - Carcinoma - Ulcerative colitis - Microscopic colitis/Lymphocyte - Diverticular disease of the colon - Haemorrhoids - Crohn’s disease - Lymphoma - Acute pancreatitis - Chronic pancreatitis - Carcinoma of the pancreas/malignant tumours - Hepatitis A - Hepatitis B - Hepatitis C - Chronic hepatitis - Alcoholic liver disease/cirrhosis - Non alcoholic steathohepatitis (NASH) - Haemochromatosis - Hepatocellular carcinoma - Acute and chronic cholecystitis - Cholelithiasis - Cholangiocarcinoma - Alcohol and the gut - The gut in Aids - The gut in systemic disorders.